Genetic analysis of resistance to Karnal bunt caused by Neovossia indica in bread wheat (Triticum aestivum) - TYAGI, B S; SHORAN, JAG; SINGH, S K; SAHARAN, M S; KUMAR, J; SINGH, GYANENDRA; SINGH, MANGAL; SHARMA, SUDHIR (The Indian Journal of Agricultural Sciences, 2010)
The genetics of Karnal bunt resistance was studied in populations derived from crosses involving resistant stocks (‘HD 29’ and ‘WL 6975’) and 1 highly susceptible cultivar (‘WL 711’). The plant material screened for Karnal bunt reaction consisted of F1, F2, BC1 and BC2 populations from resistant × susceptible and resistant × resistant crosses. The data recording for Karnal bunt incidence was done under optimal conditions for disease development with a mixture of virulent isolates prevailing in the northern states, Punjab, Haryana, Uttaranchal, Delhi, Himachal Pradesh and western Uttar Pradesh. The generation means analysis and scaling test was performed. In all the 3 cross combinations, almost all the scaling tests were found significant which indicated the presence of all 3 type of interactions. Six parameter model indicated the additive as well as dominance effects of genes significant in crosses obtained involving reaction types of resistant × susceptible (‘HD 29’ × ‘WL 711’) and resistant × resistant (‘HD 29’ × ‘WL 6975’) while additive, dominance and additive × additive; dominance × dominance effects were found significant only in resistant × resistant cross (‘WL 6975’ × ‘WL 711’).